Lingual lobular capillary hemangioma. A case report - Astudillo Ramírez, Mónica (2021)
Lobular capillary hemangioma is an inflammatory hyperplasia in response to chronic irritation, resulting in an exophytic erythematous lesion due to proliferation of fibrovascular tissue. Intraorally, it can appear in any location, but it is more frequent in the gingival region. This article describes a case of a 38-year-old pregnant woman who attended the Maxillofacial Surgery Unit at San José Hospital, presenting a tumoral lesion on the right lateral area of the tongue compatible with a lobular capillary hemangioma. The diagnosis was confirmed with histopathology. The aim of this report is to specify the characteristics and treatment of a lesion with infrequent location.